Counseling on The Importance of The Diction of “Side Dishes Amis-Amis” for Pregnant, Breastfeeding Women and Toddler for Preventing Bad Nutrition and Stunting in Kalisat Village, Jember District, East Java - Asrumi; Asri Sundari; Anastasia Erna R.S.; I.G. Krisnadi; Imam Basuki; Hanny Rasni; Sofia (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
Jember Regency ranks 8th in East Java and 11th in Indonesia for cases of malnutrition and stunting in infants. Kalisat District is among the top 5 for stunted babies in Jember. The root of the problem is not only the local economy but also the public's understanding of the term "nutrition," which is not yet reflected in daily life. Therefore, counseling on understanding the word nutrition, replaced with "amis-amis or mis-amis" for various high-protein side dishes, is essential. The young mothers in Jember had poor understanding and very low reflection on the term nutrition, contributing to malnutrition and stunting in Kalisat Village, Kalisat District. The solution is to conduct counseling and practical sessions on the importance of understanding the term "fishy side dishes" that are high in animal protein for pregnant and breastfeeding mothers to enhance brain and physical growth (fetal) and avoid malnutrition and stunting. The methods of implementation include observation, interviews (in FGD), counseling, and practical sessions in Kalisat Village, Jember. The results show that community service involving counseling or socialization of the understanding of the word nutrition, implemented through the replacement of the term with "fishy side dishes," is more effective. This approach includes FGD, counseling, and practical sessions of cooking and eating together using high-protein fishy side dishes. These methods are aimed at improving growth and development in children (from the womb, during breastfeeding, and in toddlers) to prevent malnutrition and stunting.